Constitutional Review of Regulations and Bylaws in the Saudi Legal System - Sulafa Siddig Ali Yousif (International Journal of Law Research and Studies, 2026)
This study aims to highlight the mechanisms of “Constitutional Review of Regulations and Bylaws in the Saudi Legal System,” in light of the rapid legislative and regulatory renaissance witnessed by the Kingdom of Saudi Arabia under Vision 2030. The problem of the study stems from the need to root and identify the entities and institutions tasked with verifying the compatibility of regulations (laws) and subsidiary bylaws with the supreme principles established in the Basic Law of Governance, especially in the absence of a specialized and independent constitutional court. The study adopted an analytical-inductive approach to the texts of the Basic Law of Governance and relevant judicial systems, while tracking the judicial applications issued by the Board of Grievances (Administrative Judiciary) and ordinary courts. The study reached several findings, most notably: that constitutional review in the Kingdom finds its solid ground in the supremacy of Sharia and regulatory rules, and that the administrative judiciary plays an active and decisive role in reviewing the constitutionality and legality of bylaws and executive decisions through the review of abstention or annulment, while regulations are subject to prior and subsequent review mechanisms by the regulatory authority. The study recommends the importance of developing regulatory frameworks and unifying the judicial reference for ruling on pleas of unconstitutionality to enhance the efficiency of the legislative structure.
Keywords: Constitutional oversight; Basic Law of Governance; Regulations and Bylaws; Saudi System; Board of Grievances